Análise da correlação entre o tempo para o primeiro ortostatismo e a capacidade de deambulação na alta da UTI adulto - Pereira, Gabriela (2025)
The number of individuals who survive admission to adult ICUs has been gaining notoriety due to its increase. However, the mortality rate should not be used as the only predictive factor to assess the good impact of treatment, but also the functional status at which they return to society. The aim of this study was to analyze the correlation between the date of the first orthostatism and the functional capacity of ambulation at discharge from the adult ICU. This is a retrospective observational cohort study with a convenience sample (n = 578), carried out in the adult ICU of a University Hospital between January and December 2023. Data were expressed as mean, standard deviation, median, quartiles, frequency and percentage. Age, ICU time and time to the 1st orthostatism were correlated by the T-test. Pearson's correlation was used to associate the time to the 1st orthostatism with age, ICU time and variation in the JH-HLM (p < 0.05). The study showed a longer average time to reach the first orthostatism for those who did not show walking activity at discharge, as well as a strong positive correlation between the time to reach the first orthostatism and the total length of stay of patients in the ICU.